Culicoides baniwa sp.nov. from the Brazilian Amazon Region with a synopsis of the hylas species group (Diptera: Ceratopogonidae) - Felippe Bauer, María Luiza (2009)
A new species of the Culicoides (Hoffmania) hylas species group, Culicoides baniwa Felippe-Bauer is described and illustrated based on a female specimen from the state of Amazonas, Brazil. A systematic key, wing photographs, diagramme of the legs pattern, table with numerical characters of females and a synopsis of the 11 species of the C. hylas group are presented. This paper further presents a new record of Culicoides pseudoheliconiae Felippe-Bauer out of the previously defined geographic distribution of the hylas species group, in the province of Misiones, Argentina.